(untitled) (International relations and international law Journal, 2016)
It this article the author considers policy of Russia in Central Asia during Boris Yeltsin presidency, when the Russian Federation "was going to leave"Central Asia. This step led to the breaking of economic relations between Russia and CAR countries. Statesin the region had to search new cooperation areas for the development of the economies of their countries.The only sector in which Russia tried to preserve its influence was an oil and gas sector, but by the late 1990s the Russian Federation had to compete with other influential regional actors. With the change in foreign policy strategy of Russia, attitude of the Russian Federation to the Central Asian states has also varied. The Russian Federation seeks to restore its presence in the region, including economic sphere, but now it is one of many states with which the Central Asian states are ready to build economic relations, and under the set of parameters RF inferior to its competitors in the struggle for the region’s economy.